Multiplexed longitudinal analysis of the cellular and microbial dynamics of acute polymicrobial sepsis in mice - Peacock, Tori E.; Johnson, Kenny; Cheedipudi, Abhinav R.; Mohammed, Ahmed D.; Ball, Ryan A. W.; Cox, J. Hunter; Pender, Savannah K.; Jolly, Amy; Velázquez, Kandy T.; Potts, Jay; Murphy, Angela; Frizzell, Norma; et al. (Frontiers in Immunology, 2025)
IntroductionAcute polymicrobial sepsis is a life-threatening emergency caused by the body’s immune response to bloodstream infection by two or more microbes. Early detection and management of sepsis have been the focus of global survey programs, driven by its association with hospital readmissions and long-term adverse health outcomes.MethodsAnimal models are essential tools for studying mechanisms of sepsis pathogenesis and the only way to empirically dissect the acute phase of disease. With this in mind, the goal of the current study was two-fold: to demonstrate the feasibility of performing multiplexed longitudinal assessment of acute sepsis pathogenesis and to emphasize the granularity with which acute sepsis can be studied using this method. Using the fecal suspension test (FST) model of acute polymicrobial sepsis in C57BL/6 mice we simultaneously characterize hematological, immunological, and microbiological aspects of acute sepsis induction.ResultsOur data shows that high dimensional flow cytometry paired with flow-based plasma cytokine measurements captures the dynamic shift from pro-inflammatory to anti-inflammatory immune responses during an acute septic event; highlighting the role of emergency myelopoiesis in this process. Additionally, myeloid cell heterogeneity is characterized and strongly implicates the emergence of myeloid derived suppressor like cells (MDSC-like cells) as central to this switch. Furthermore, we demonstrate a 16S-based method for studying the blood biome that allows for discrimination between endogenous (bacterial DNAemia) and exogenous (actively growing bacteria in blood) sources of microbial DNA. Using this approach, we demonstrate that polymicrobial sepsis in our model is due to outgrowth of Enterococcus and Staphylococcus; two genera of bacterial pathobionts commonly observed in human sepsis patients. Finally, using several assessments of disease severity, we demonstrate stratification of septic mice into survivors and non-survivors and show how pre-septic immune assessment can be used to identify potential biomarkers of sepsis risk.DiscussionCollectively, the approach we describe simultaneously reduces research animal use, strengthens scientific rigor, provides a pre-clinical platform for biomarker discovery and the study of therapeutic interventions, and most importantly advances our ability to study the acute phase of sepsis that carries a high mortality rate and is difficult to prospectively study in humans.